PENERAPAN KLAUSUL EKSONERASI DAN AKIBAT HUKUMNYA DALAM PERJANJIAN PEMBIAYAAN MUSYARAKAH PADA BANK SYARIAH (Studi Putusan Pengadilan Agama Nomor 967/Pdt.G/2012/PA.Mdn) - Nurjannah Nurjannah; Tan Kamello; Hasim Purba; Utary Maharany Barus (USU LAW JOURNAL, 2016)
ABSTRACT The implementation of exoneration clause in the judicial viewpoint of the Islamic Contract was contrary to Al-Qur’an, Hadits, and sharia principles like tyrannical aspect which could cause injustice for the parties concerned. Exoneration clause is also contrary to the principles in the Islamic Contract. The legal consequence of the implementation of exoneration clause in the Islamic Contract is a bad contract. In the Civil Code, Law on Consumer Protection, and the Rule of Financial Services Authority is null and void. The implementation of exoneration clause in the statement letter on musyarakah (capital participation) financing contract in the case of the Religious Court Number 967/Pdt.G/2012/PA.Mdn, the judges have applied the law to decide the exoneration clause does not have the binding force on the parties, so that the repayment of the financing is not the responsibility of the heir.   Keywords: Exoneration Clause, Legal Consequence, Musyarakah Financing.